Maternal Serum Soluble CD30 Is Increased in Normal Pregnancy, but Decreased in Preeclampsia and Small for Gestational Age Pregnancies - Kusanovic, Juan Pedro (2007)
OBJECTIVE: Women with preeclampsia and those who deliver small for gestational age (SGA) neonates are characterized by intravascular inflammation (T helper 1 (Th1)-biased immune response). There is controversy about the T helper 2 (Th2) response in preeclampsia and SGA. CD30, a member of the tumor necrosis factor receptor superfamily, is preferentially expressed in vitro and in vivo by activated T cells producing Th2-type cytokines. Its soluble form (sCD30) has been proposed to be an index of Th2 immune response. The objective of this study was to determine whether maternal serum concentration of sCD30 changes with normal pregnancy, as well as in mothers with preeclampsia and those who deliver SGA neonates. METHODS: This cross-sectional study included patients in the following groups: (1) non-pregnant women (N=49); (2) patients with a normal pregnancy (N=89); (3) patients with preeclampsia (N=100); and (4) patients who delivered an SGA neonates (N=78). Maternal serum concentration of sCD30 was measured by a specific and sensitive enzyme-linked immunoassay. Non-parametric tests with post-hoc analysis were used for comparisons. A p value <0.05 was considered statistically significant. RESULTS: (1) The median sCD30 serum concentration of pregnant women was significantly higher than that of non-pregnant women (median: 29.7 U/mL, range: 12.2-313.2 vs. median: 23.2 U/mL, range: 14.6-195.1, respectively; p=0.01); (2) Patients with preeclampsia had a significantly lower median serum concentration of sCD30 than normal pregnant women (median: 24.7 U/mL, range: 7.6-71.2 vs. median: 29.7 U/mL, range: 12.2-313.2, respectively; p<0.05); (3) Mothers with SGA neonates had a lower median concentration of sCD30 than normal pregnant women (median: 23.4 U/mL, range: 7.1-105.3 vs. median: 29.7 U/mL, range: 12.2-313.2, respectively; p<0.05); and (4) There was no significant correlation (r=-0.059, p=0.5) between maternal serum sCD30 concentration and gestational age (19-38 weeks) in normal pregnant women. CONCLUSIONS: (1) Patients with preeclampsia and those who deliver a SGA neonate had a significantly lower serum concentration of sCD30 than normal pregnant women; (2) This finding is consistent with the view that preeclampsia and SGA are associated with a polarized Th1 immune response and, perhaps, a reduced Th2 response.